If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -15 = (2x + 10) Reorder the terms: -15 + 3x = (2x + 10) Reorder the terms: -15 + 3x = (10 + 2x) Remove parenthesis around (10 + 2x) -15 + 3x = 10 + 2x Solving -15 + 3x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -15 + 3x + -2x = 10 + 2x + -2x Combine like terms: 3x + -2x = 1x -15 + 1x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 -15 + 1x = 10 + 0 -15 + 1x = 10 Add '15' to each side of the equation. -15 + 15 + 1x = 10 + 15 Combine like terms: -15 + 15 = 0 0 + 1x = 10 + 15 1x = 10 + 15 Combine like terms: 10 + 15 = 25 1x = 25 Divide each side by '1'. x = 25 Simplifying x = 25
| 6x+10=6x | | 2.7x+13.758=4-2.97x | | 4-2m+4m+1= | | 8+5y=24 | | 4*x=2.5 | | (-x+9)*4= | | 7a-20=80 | | 3(2y+5)=30 | | 23x-5=25x-5 | | 2x+5=133 | | Y=58x+228 | | 7=5k-3 | | 5x-1=-5x+1 | | 7/2*63=7/2*2/7 | | M-5=11 | | (-x+7)*3= | | (g-7)(g+9)= | | 4v=8e-g | | 10m+3=38 | | 0.9=-log | | 2*-1=0 | | -2x^2-22x+24= | | 4v=8e | | 2x+2=0.50x+11 | | 5a+12=36 | | 3n-5n=3 | | (7x-6)=90 | | 5/7x35 | | 5(2x+6)=-3(4x-1) | | 4(m-2)=14 | | (4x+3)+(-2x+4)=y | | 4.7p+8.7p+2.6p=93.96 |